Этнолингвистические и типологические параллели в фольклорном творчестве народов (на материале свадебно-обрядовых песен башкир) - Султангареева, Розалия (Acta Polono-Ruthenica, 2018)
In Turkic (Bashkir) wedding folklore, in the heritage of world spiritual culture, centuries-old knowledge of philosophy, life-concepts and ideals, as well as language, etiquette, moral and moral values of peoples are concentrated. This article covers the wedding and ritual culture of the Turks and Slavs. Using Bashkir ritual as an example, typological features and parallels in folklore genres associated with common situations of marriage festivals, clan interests and emotions are revealed. Wedding genres of lamentations, good wishes and praise, whose origins go back to the magic of kind words, tears and crying after a complex transformation, create a picture of universal ritual codes.